The Relationality of Rules of Debit and Credit - Sony Warsono (The Indonesian Journal of Accounting Research, 2015)
Abstract : Double-entry bookkeeping (DEB) and the rules of debit and credit (RDC) have been used in practice and taught in academia for at least 500 years. In the journal Issues in Accounting Education, certain scholars have debated whether RDC needs to be eliminated from introductory accounting courses. The proponents argue that teaching RDC bears greater costs than benefits and that the rules are not intuitive for most students. Conversely, the opponents argue that RDC is fundamental knowledge in accounting and has been shown to survive without many changes. The unfinished nature of the debate was partly due to the absence of the objective rationality of RDC. This paper shows that DEB and RDC have a close relation mathematically. Initially, this paper presents speci fic essential facts regarding double-entry bookkeeping as a vast knowledge that should be respected by modern accounting scholars.Furthermore, this paper presents the rationality of RDC. This rationality is based on a mathematical perspective because RDC was documented in the book of mathematics and written by a professor of mathematics. RDCs are applied to address the writings on the reduction of monetary value. Kata Kunci : Pembukuan double-entry (DEB) dan aturan debit dan kredit (RDC) telah digunakan dalam praktek dan diajarkan di dunia akademis setidaknya selama 500 tahun. Dalam jurnal Masalah dalam Pendidikan Akuntansi, sarjana tertentu telah diperdebatkan apakah RDC perlu dihilangkan dari kursus akuntansi pengantar. Para pendukung berpendapat bahwa mengajar RDC menanggung biaya yang lebih besar daripada manfaat dan bahwa aturan tidak intuitif untuk sebagian besar siswa. Sebaliknya, lawan berpendapat bahwa RDC adalah pengetahuan dasar dalam akuntansi dan telah terbukti bertahan tanpa banyak perubahan. Sifat perdebatan yang belum selesai sebagian karena tidak adanya rasionalitas obyektif RDC. Makalah ini menunjukkan bahwa DEB dan RDC memiliki hubungan yang erat secara matematis. Awalnya, makalah ini menyajikan fakta-fakta penting spesifik mengenai pembukuan entri ganda sebagai pengetahuan luas yang harus dihormati oleh sarjana akuntansi modern.Selanjutnya, makalah ini menyajikan rasionalitas RDC. Rasionalitas ini didasarkan pada perspektif matematika karena RDC didokumentasikan dalam buku matematikadan ditulis oleh seorang profesor matematika. RDC diterapkan untuk mengatasi tulisan-tulisan tentang pengurangan nilai moneter.